IDENTITY THEFT IN RELATION TO CRIMINAL PROCEDURE CODE - PARTHVIRAJ, J.; ROJA, K. (International Journal of Psychosocial Rehabilitation, 2020)
As we are in the fast growing world of technologies, we have to attune ourselves to the new changes and also should be aware about its complications. Identity theft simply means use of someone else’s identity in a deliberate manner, to obtain financial benefits in the name of another or to attain him losses. Identity theft has been regarded as the top of the list of complaints by consumers nationwide to the Federal Trade Commission(FTC). One has to protect his identity as your personal information is always at risk due to the internet and complexion of technology. Some of the most common ways in which your data can be up held by someone are dark web, malware activity, credit card frauds etc. The threats have to be mitigated more effectively and efficiently as it may have disastrous impacts. There should be resilience. The aim of the research paper is to know about identity theft and its impact on public confidence. The type of research used is descriptive research and convenient sampling method is used as sampling method. The sample size is 1378. The independent variable is gender. The dependent variables are whether identity theft is a modern crime And whether identity theft prevention in the post internet era has been increased. The statistics used are independent samples t test and chi square. The study’s findings have revealed that there is a significant increase in identity theft prevention in the post internet era.